Socio-economic rights litigation as a means to engendering social change in South Africa: an introduction and context - Twinomugisha, Ben Kiromba (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2011.